2022
DOI: 10.1155/2022/7331164
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA-Sequencing Reveals the Cellular and Genetic Heterogeneity of Skin Scar to Verify the Therapeutic Effects and Mechanism of Action of Dispel-Scar Ointment in Hypertrophic Scar Inhibition

Abstract: Hypertrophic scarring (HS), caused by excessive fibrosis of injured skin, imposes a psychological burden and creates a source of distress that impairs the quality of life of affected individuals. However, the gold standard for HS treatment has not yet been determined due to the complicated and difficult nature of the routines and procedures involved. Previous studies have indicated that the topical application of certain active components found in traditional Chinese medicines shows potential as a therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…SP and FC are often applied in combination to treat blood stasis syndrome such as amenorrhea due to stagnation of blood, dysmenorrhea, postpartum abdominal pain due to blood stasis, abdominal pain due to abdominal mass, and traumatic injury and swelling (Liu et al, 2015). The research by Zhaoyi Li et al revealed that the dispel-scar ointment, prepared from Chinese herbs such as SP, FC, and motherwort, could effectively promote scar maturation and reduce scar area (Li et al, 2022). Wang et al used SP source plaster in a nude mouse transplantable model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SP and FC are often applied in combination to treat blood stasis syndrome such as amenorrhea due to stagnation of blood, dysmenorrhea, postpartum abdominal pain due to blood stasis, abdominal pain due to abdominal mass, and traumatic injury and swelling (Liu et al, 2015). The research by Zhaoyi Li et al revealed that the dispel-scar ointment, prepared from Chinese herbs such as SP, FC, and motherwort, could effectively promote scar maturation and reduce scar area (Li et al, 2022). Wang et al used SP source plaster in a nude mouse transplantable model.…”
Section: Introductionmentioning
confidence: 99%
“…The research by Zhaoyi Li et al. revealed that the dispel‐scar ointment, prepared from Chinese herbs such as SP, FC, and motherwort, could effectively promote scar maturation and reduce scar area (Li et al., 2022). Wang et al.…”
Section: Introductionmentioning
confidence: 99%